2020
DOI: 10.1002/jsfa.10422
|View full text |Cite
|
Sign up to set email alerts
|

Fruit quality and major metabolites in cold‐stored ‘Wonhwang’ Asian pears are differentially affected by fruit size

Abstract: BACKGROUND: The size of 'Wonhwang' Asian pear fruit may affect fruit quality and physiological disorders differentially during distribution. Thus, this study aimed to evaluate the effect of fruit size on fruit physiological attributes and metabolic responses in terms of soluble carbohydrates and free amino acids in different-sized 'Wonhwang' Asian pears during cold storage and shelf life. RESULTS: The rate of weight loss and the severity of fruit shriveling were higher in small fruit than in large fruit, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…After the fruit is picked, the quality may change depending on the storage condition before entering the consumer's table (Karagiannis, 2018;Wu et al, 2019Wu et al, , 2021Lwin and Lee, 2020;Fuentealba, 2021). Comparing the changes of volatile compounds before and after 7 days of storage of 3 hairy peaches (Prunus persica L.) and 3 nectarines, it was found that the distribution of volatile compounds in fruits tended to be similar after storage.…”
Section: Fruit Quality Formationmentioning
confidence: 99%
“…After the fruit is picked, the quality may change depending on the storage condition before entering the consumer's table (Karagiannis, 2018;Wu et al, 2019Wu et al, , 2021Lwin and Lee, 2020;Fuentealba, 2021). Comparing the changes of volatile compounds before and after 7 days of storage of 3 hairy peaches (Prunus persica L.) and 3 nectarines, it was found that the distribution of volatile compounds in fruits tended to be similar after storage.…”
Section: Fruit Quality Formationmentioning
confidence: 99%
“…However, in ‘Gala’ apple cultivar, as the fruits size, the respiration rate increases 43 . Conversely, the asian pear cultivar ‘Wonhwang’ respiration rate was lower in large fruits compared to small fruits 44 . Also, Richings et al 45 .…”
Section: Discussionmentioning
confidence: 96%
“…43 Conversely, the asian pear cultivar 'Wonhwang' respiration rate was lower in large fruits compared to small fruits. 44 Also, Richings et al 45 reported a higher respiration rate in small-fruited 'Hass' avocado fruit. Similar results were also found in guava fruit, 46 unlike Rahayu and Bintoro.…”
Section: Discussionmentioning
confidence: 98%
“…In order to differentiate the quality of untreated, HHP-treated, pasteurization-treated and pasteurization-HHP-treated milk from an overall perspective, the raw data of physicochemical characteristics, nutrient content and sensory quality were subjected to PCA analysis. PCA was supported by MetaboAnalyst, which was accessible at , according to Lwin et al [ 28 ], and the analysis was performed using the prcomp package.…”
Section: Methodsmentioning
confidence: 99%